PLASTIC MONEY: PROSPECTIVE AND CHALLENGES - Mukaria, Bhawna (International Journal of Engineering Technologies and Management Research, 2018)
In present era, it is impossible to imagine modern bank transactions, commercial transactions and other payments without using the plastic cards. Plastic currency is now gradually becoming a necessity across the globe as more and more developed countries are opting for plastic compared to paper as there are several inherent advantages. The growing involvement of smart phones has made technology applications much more accessible to users. The Government also move forward for a “Digital India” and its focus on growing electronic payments is significant drivers of growth in replacing physical payments with technologybacked solutions. India is at the stage of an amazing shift towards electronic money from traditional cash. For instance the Pradhan Mantri Jan Dhan Yojana (PMJDY), is slowly building recognition among people to move from paper to electronic money. The PMJDY alone has seeded over 150 million Rupay cards in the last year, in addition to the 400 million debit cards already in circulation. There is still emergence for significant increase in the usage of debit cards in the years to come as card. This paper focus on the challenges and future prospects of plastic money in India.